2015
DOI: 10.1007/s10964-014-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Specificity in the Relationship between Maternal Autonomy Support and Children’s Socio-emotional Development: A Longitudinal Study from Preschool to Preadolescence

Abstract: The benefits of an autonomy supportive environment have been established as a key component in children's development at various ages. Nonetheless, research examining the outcomes of early autonomy supportive environments has largely neglected socio-emotional development. The first objective of the present longitudinal study was to examine the socio-emotional outcomes associated with maternal autonomy support during the preschool period. Second, we explored the contextual specificity of the relationships betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 66 publications
0
43
0
Order By: Relevance
“…Many different factors infl uence children's development, and children are infl uential actors in their own development. Nonetheless, parents unequivocally infl uence children's development before they are born, contributing to children's biobehavioral patterns that begin early in life-infl uences that have been found to persist into middle childhood and beyond (Klasen et al, 2015;Matte-Gagné, Harvey, Stack, & Serbin, 2015;Sroufe, 2005). Thus, the foundations of children's developmental trajectories are rooted in their early environments, which are defi ned by parents-for better or worse.…”
Section: Fundamentals Of Parenting Competencementioning
confidence: 99%
“…Many different factors infl uence children's development, and children are infl uential actors in their own development. Nonetheless, parents unequivocally infl uence children's development before they are born, contributing to children's biobehavioral patterns that begin early in life-infl uences that have been found to persist into middle childhood and beyond (Klasen et al, 2015;Matte-Gagné, Harvey, Stack, & Serbin, 2015;Sroufe, 2005). Thus, the foundations of children's developmental trajectories are rooted in their early environments, which are defi ned by parents-for better or worse.…”
Section: Fundamentals Of Parenting Competencementioning
confidence: 99%
“…Maternal sensitivity involves congruency of emotional expressions and interpreting the emotional cues of the infant appropriately, whereas maternal structuring involves sensitivity to the infant's abilities and limitations, while also creating appropriate boundaries and setting limits for inappropriate behavior (Ainsworth, Blehar, Waters, & Wall, ; Biringen et al., ; Perry, Mackler, Calkins, & Keane, ; Smith & Pederson, ). Both dimensions play a role in supporting the infant's autonomy so that the infant is comfortable exploring the environment, and looking to the mother for support when needed (Matte‐Gagné, Harvey, Stack, & Serbin, ). In contrast, infants' development of expectations is hindered when their cues are misinterpreted or ignored (Bronson, ).…”
Section: Quality Of the Mother–infant Relationshipmentioning
confidence: 99%
“…Some longitudinal studies showed that adolescents’ perceived autonomy support predicted decreasing internalizing problems two years later (Bloemert, ). The less parents provided autonomy support at time 1, the more children reported internalizing problems at time 2 and time 3 (Matte‐Gagné, Harvey, Stack & Serbin, ). In a comprehensive view, parental autonomy support may function as a protector, mitigating the negative effect of psychological control on adolescents’ adjustment outcomes (Inguglia, Ingoglia, Liga et al ., ).…”
Section: Introductionmentioning
confidence: 99%